Snow Stable Isotope Composition Variability Related to the Upper Mendoza River Basin Hypsometry - Crespo, Sebastián Andrés; Aranibar, Julieta Nelida; Navarro, Gonzalo (International Journal of Advanced Research in Chemical Science)
The water supply of the northern oasis of the Mendoza province, in the central western of Argentina, depends mainly on the melting of precipitated and accumulated snow during the winter, which supplies water for domestic, industrial and energy consumption to 64% of the provincial population (more than 1.2 million inhabitants). The solid precipitation stable isotopes composition in mountain regions is affected by isotopic fractionation processes generated by continentally effects, temperature, evaporation during precipitation and isotopic elution phenomena during melting, among others, complicating efforts to quantify sources using stable isotopes as natural tracers. The aim of this work was to evaluate the stable isotopes composition of snowfall in an altitude gradient in the Cordillera Principal, Upper Mendoza River basin. We did not find an altitude effect on stable isotope composition of snow, widely reported in previous studies. Variability was related to the origin of precipitation events. These results validate the use of stable isotopes as tracers of different water sources as glaciers, permafrost, groundwater or snow in Cordillera Principal, to quantify contributions from different sources to riverflow. Fil: Crespo, Sebastián Andrés. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina. Pontificia Universidad Católica de Valparaíso; Chile Fil: Aranibar, Julieta Nelida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto ...